1樓:現舞
a:5(x-5)+2=-4
5x-25+2=-4
5x=19
x=19/5
b:3(x-2)=(8-8x)
3x-6=8-8x
11x=14
x=14/11
c:3x-12+4(x-3)=2(x+1)-53x-12+4x-12=2x+2-5
7x-24=2x-3
5x=21
x=21/5
d:3x-2(x+2)=4(x-1)+7
3x-2x-4=4x-4+7
x-4=4x+3
-3x=7
x=-7/3
e:3x-2[x-5(x+1)-4]=4
3x-2[x-5x-5-4]=4
3x-2[-4x-9]=4
3x+8x+18=4
11x=-14
x=-14/11
f:4/3[3/4(1/5x-2)-6]=1(1/5x-2)-8=1
1/5x=11
x=55
g:3(x+5)+5[(x+5)-1]=7(x+5)-13(x+5)+5(x+5)-5=7(x-5)-18(x-5)-7(x-5)=4
x-5=4
x=9h:
5(2-3x)=4(x+1)
10-15x=4x+4
-19x=-6
x=6/19
i:3-2(x-1)=2(x-3)
3-2x+2=2x-6
-4x=-11
x=11/4
j:1/3(6x-3)-1/2(8x-4)=52x-1-4x+2=5
-2x=4
x=-2
k:(3x+2)+2[(x-1)-(2x+1)]=63x+2+2(x-1)-2(2x+1)=63x+2+2x-2-4x-2=6
x=8l:
3x-2/5=x+1/2
3x-x=1/2+2/5
2x=5/10+4/10
2x=9/10
x=9/20
m:4(x+2)/3-x-7/5=12
(4x+8)/3-x-7/5=12
4x/3+8/3-x-7/5=12
x/3=12+7/5-8/3
x=36+21/5-8
x=28+21/5=161/5
n:t-t-1/2=2-t+2/3
-1/2=2-t+2/3
t=8/3+1/2
t=16/6+3/6
t=19/6
o:3x-2(x+3)/3=6-x-2/63x-2x/3-2=6-x-1/3
7x/3-2=-x+6-1/3
10x/3=8-1/3
10x=25
x=5/2
p:3/2[2/3(x/4-1)-2]-8=x2/3[x/6-2/3-2]-8=x
x/9-4/9-4/3-8=x
x-4-12-72=9x
-8x=88
x=-11
q:2x+1/3-5x-1/6=1
12x+2-30x-1=6
-18x=5
x=-5/18
r:3(2x+1)/4-2(2x-1)/3=19(2x+1)-8(2x-1)=12
18x+9-16x+8=12
2x=-5
x=-5/2
s:y-y-1/2=2-y+2/5
-1/2=2-y+2/5
y=2+2/5+1/2
y=20/10+4/10+5/10
y=29/10
2樓:帳號已登出
解;a. 5(x-5)=-6 x-5=-1.2 x=3.
8b. 3x-6=8-8x 11x=14 x=14/11c. 3x-12+4x-12=2x+2-5 5x=21 x=21/5
d. 3x-2x-4=4x-4+7 -3x=7 x=-7/3
解下列方程
公式法?1 x 10x 9 0 x 10x 25 16 x 5 16 x 5 4 x1 1,x2 9 3 3x 6x 4 0 3 x 2x 1 4 3 0 3 x 1 7 x 1 21 3 x1 21 3 1 x2 21 3 1 5 x 4x 9 2x 11 x 2x 2 x 2x 1 1 x 1 ...
用代入法解下列方程xy44x2y
x y 4 所以,x y 4 代入到第二個方程有 4 y 4 2y 1 4y 16 2y 1 6y 17 y 17 6 所以,x y 4 17 6 4 7 6 x y 4 代入 4 y 4 2y 1 4y 2y 1 16 6y 17 y 17 6 x 4 17 6 x 4 y 4x 4 y 2y 1...
解下列方程 1 4 x 3 2 25 x
1 4 x 3 2 25 x 2 2 0 解 4 x 2 1 2 25 x 2 2 0 4 x 2 2 8 x 2 4 25 x 2 2 0 21 x 2 2 8 x 2 4 0 3 x 2 2 7 x 2 2 0 x1 4 3,x2 16 7 2 2x 1 2 4 2x 1 4 解 2x 1 2 ...